Qualitative study of the influence of horse‐owner relationship during some key events within a horse's lifetime. (28th January 2021) - Clough, Harriet; Roshier, Mandy; England, Gary; Burford, John; Freeman, Sarah
Abstract: Background : There is a lack of research exploring how the horse‐human relationship influences horse owners' decision‐making. The aim of this study was to investigate how an owner's relationship with their horse affects decisions around key events during their horse's lifetime. Methods : An online survey and semi‐structured telephone interviews were conducted with horse‐owners. The online survey asked horse owners about their experiences of decision‐making and their relationship with their horse and identified interview participants. Two semi‐structured interviews were conducted with 11 horse owners on their experience of purchasing and euthanasia of horses. Interviews were recorded and transcribed, and thematic analysis was performed. Results : There were 938 responses to the online survey. The majority of owners considered their horse to be a member of the family (92.9%, 808/870). The mean amount spent annually on their horse was £9215 (range £324–14, 240). Seven themes were identified in the interviews including mismatching of horse and rider; financial, time, welfare and personal obligations involved in horse ownership; shared‐decision making; the horse's quality of life; guilt and responsibility grief surrounding euthanasia decisions. Conclusion : This study highlighted the strong owner‐horse relationship, the significant obligations involved in horse ownership and the emotional impact of euthanasia decisions.